1990
DOI: 10.1073/pnas.87.22.8692
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of simian virus 40 DNA replication with purified proteins.

Abstract: Replication of plasmid DNA molecules containing the simian virus 40 (SV40) origin of DNA replication has been reconstituted with seven highly purified cellular proteins plus the SV40 large tumor (T) antigen. Initiation of DNA synthesis is absolutely dependent upon T antigen, replication protein A, and the DNA polymerase a-primase complex and is stimulated by the catalytic subunit of protein phosphatase 2A. Efficient elongation of nascent chains additionally requires proliferating cell nuclear antigen, replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(100 citation statements)
references
References 37 publications
2
98
0
Order By: Relevance
“…This was an important point to consider, as another explanation for the resistance of the full NER reaction to inhibition by p21 could be that di erent DNA polymerases are normally used for NER and for replication, with one polymerase particularly resistant to inhibition by p21. There is good evidence that replication of SV40 viral DNA in vitro requires pol d (Tsurimoto et al, 1990;Weinberg et al, 1990;Hurwitz et al, 1990), and that mammalian chromosomal replication requires both pol d and pol e (Zlotkin et al, 1996). It would be possible, for example, that NER normally functions with pol e and this enzyme is especially refractory to p21 inhibition.…”
Section: Resistance Of Ner In Human Cell Extracts To Inhibition By P21mentioning
confidence: 99%
“…This was an important point to consider, as another explanation for the resistance of the full NER reaction to inhibition by p21 could be that di erent DNA polymerases are normally used for NER and for replication, with one polymerase particularly resistant to inhibition by p21. There is good evidence that replication of SV40 viral DNA in vitro requires pol d (Tsurimoto et al, 1990;Weinberg et al, 1990;Hurwitz et al, 1990), and that mammalian chromosomal replication requires both pol d and pol e (Zlotkin et al, 1996). It would be possible, for example, that NER normally functions with pol e and this enzyme is especially refractory to p21 inhibition.…”
Section: Resistance Of Ner In Human Cell Extracts To Inhibition By P21mentioning
confidence: 99%
“…Biochemical studies using the SV40 DNA replication system reconstituted with purified proteins (21,24,26,54,190,191) have shown that two different polymerases, pol α/primase and pol δ, are involved in DNA synthesis and that pol δ is involved in the synthesis of both the leading and lagging strands. The switching from pol α/primase to pol δ occurs during priming of the leading strand (24) and during synthesis of every Okazaki fragment (26).…”
Section: Polymerase Switchingmentioning
confidence: 99%
“…Pol ␣/primase can only synthesize short primers that must then be extended by the activity of a processive DNA polymerase(s). Biochemical analysis of simian virus 40 (SV40) DNA replication, which has been extensively used as a model system for eukaryotic DNA replication, has shown that primers synthesized by Pol ␣ can be extended by Pol ␦ and that these two polymerases are sufficient for SV40 replication in vitro (Weinberg et al, 1990;Waga et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Pol ␣/primase can only synthesize short primers that must then be extended by the activity of a processive DNA polymerase(s). Biochemical analysis of simian virus 40 (SV40) DNA replication, which has been extensively used as a model system for eukaryotic DNA replication, has shown that primers synthesized by Pol ␣ can be extended by Pol ␦ and that these two polymerases are sufficient for SV40 replication in vitro (Weinberg et al, 1990;Waga et al, 1994).A second processive DNA polymerase, Pol ⑀, is required for cell viability and chromosomal DNA replication in both fission (D'Urso and Nurse, 1997) and budding yeast (Morrison et al, 1990;Araki et al, 1992;Budd and Campbell, 1993). Pol ⑀ has also been implicated in both DNA repair (Jessberger et al, 1993;Wang et al, 1993;Shivji et al, 1995;Holmes, 1999) and cell cycle checkpoint control in eukaryotic cells (Navas et al, 1995).…”
mentioning
confidence: 99%